Comparison of MICs in Escherichia coli isolates from human health surveillance with MICs obtained for the same isolates by broth microdilution. Issue 3 (21st September 2021) - Suwono, Beneditta; Hammerl, Jens André; Eckmanns, Tim; Merle, Roswitha; Eigner, Ulrich; Lümen, Michaela; Lauter, Sven; Stock, Rüdiger; Fenner, Ines; Boemke, Eva; Tenhagen, Bernd-Alois
Abstract: Objectives: Human health surveillance and food safety monitoring systems use different antimicrobial susceptibility testing (AST) methods. In this study, we compared the MICs of Escherichia coli isolates provided by these methods. Methods: E. coli isolates ( n = 120) from human urine samples and their MICs were collected from six medical laboratories that used automated AST methods based on bacterial growth kinetic analyses. These isolates were retested using broth microdilution, which is used by the food safety monitoring system. The essential and categorical agreements (EA and CA), very major errors (VME), major errors (ME) and minor errors (mE) for these two methods were calculated for 11 antibiotics using broth microdilution as a reference. For statistical analysis, clinical breakpoints provided by EUCAST were used. Results: Five study laboratories used VITEK ® 2 and one MicroScan (Walkaway Combo Panel). Out of 120 isolates, 118 isolates (98.3%) were confirmed as E. coli . The 99 E. coli isolates from five study laboratories that used VITEK ® 2 showed high proportions of EA and CA with full agreements for gentamicin, meropenem, imipenem and ertapenem. Additionally, 100% CA was also observed in cefepime. Few VME (0.5%), ME (1.9%) and mE (1.5%) were observed across all antibiotics. One VME for ceftazidime (7.1%) and 12 MEs for ampicillin (29.4%), cefotaxime (2.4%), ciprofloxacin (3.2%), tigecycline (1.5%) and trimethoprim (22.2%) were detected. Conclusions: MICs from E. coli isolates produced by VITEK ® 2 were similar to those determined by broth microdilution. These results will be valuable for comparative analyses of resistance data from human health surveillance and food safety monitoring systems.